Epigenetic and molecular signatures of cord blood CD34+ cells treated with histone deacetylase inhibitors. Issue 1 (17th June 2015) - Gajzer, D.; Ross, J.; Winder, L.; Navada, S.; Zhang, W.; Silverman, L.; Chaurasia, P.
Abstract : Background and Objectives: Epigenetic modifications tightly regulate the gene expression and cellular function of haematopoietic stem cells. Histone deacetylase inhibitors (HDACIs) alter the gene expression profile of cord blood (CB) CD34 + cells by controlling the genes involved in chromatin modification, thereby influencing the self‐renewal, maintenance and expansion of haematopoietic stem and progenitor cells (HSPCs). Materials and Methods: The class I and II HDACIs, valproic acid and scriptaid, were utilized to expand CB‐CD34 + cells ex vivo. The gene profiling was performed on HSPC using Illumina microarray, GeneGO MetaCore ™ and Ingenuity pathway analyses. The molecular analyses were performed using Q‐PCR and Western blotting. Results: Each HDACI treatment of CB‐CD34 + cells created unique epigenetic and molecular signatures that governed chromatin modification required for cellular and functional behaviour of stem cells. GeneGO MetaCore ™ and Ingenuity pathway analyses established the molecular understanding of epigenetically regulated HSPCs in the presence of scriptaid and VPA that revealed different network(s) of potential regulators during erythropoiesis. VPA induced transcriptional activation of the glucocorticoid receptor (GCR) and an increase in the intracellular signalling of signal transducers and activators of transcription (STAT) required during stress erythropoiesis. Canonical Wnt signalling and many epigenetically regulated chromatin remodellers were significantly influenced so as to establish maintenance and regulation of HSPC. Conclusion: Treatment with Individual HDACIs has demonstrated significantly unique epigenetic and molecular signatures of CB‐HSPC. This study identifies potential key regulators of HSPC and gives insights into the clinically important processes of HSPC expansion and haematopoietic lineage development for transplantation purposes.